The Extracellular Matrix in Skin Inflammation and Infection - Pfisterer, Karin; Shaw, Lisa E.; Symmank, Dörte; Weninger, Wolfgang (Frontiers in Cell and Developmental Biology, 2021)
The extracellular matrix (ECM) is an integral component of all organs and plays a pivotal role in tissue homeostasis and repair. While the ECM was long thought to mostly have passive functions by providing physical stability to tissues, detailed characterisation of its physical structure and biochemical properties have uncovered an unprecedented broad spectrum of functions. It is now clear that the ECM not only comprises the essential building block of tissues but also actively supports and maintains the dynamic interplay between tissue compartments as well as embedded resident and recruited inflammatory cells in response to pathologic stimuli. On the other hand, certain pathogens such as bacteria and viruses have evolved strategies that exploit ECM structures for infection of cells and tissues, and mutations in ECM proteins can give rise to a variety of genetic conditions. Here we review the composition, structure and function of the ECM in cutaneous homeostasis, inflammatory skin diseases such as psoriasis and atopic dermatitis as well as infections as a paradigm for understanding its wider role in human health.